ANALISIS PRODUKSI PADI DI KABUPATEN KENDAL (Studi Kasus Kecamatan Limbangan Kabupaten Kendal) - Pasca Tentoea, Adelino; Rejekiningsih, Tri Wahyu (Diponegoro Journal of Economics, 2013)
Paddy is one of the results of the agricultural food crops. Paddy is the most important food crop for the people especially the people of Indonesia. Paddy is the food source of carbohydrates and contain the necessary nutrients the human body. Limbangan districts is one of the rice-producing districts located in Kendal regency, Central Java.This study has the objective to analyze the resulting rice production in Sub Limbangan, Kendal. Variables - variables used in the study is the wide breadth of the land, labor, fertilizer and pesticides. To support the data in this study using primary data and secondary data. In sampling using proportional sampling. The analytical method used is the method of least squares (Ordinary Least Squares / OLS) regression model produces an estimator of the best linear unbiased (Best Linear Estimator Unbiased / BLUE).In the regression calculation showed high R2 value of 0.912. Based on the results of this study showed that the variables of land, labor, fertilizer and pesticide significant effect on the amount of rice production in Sub Limbangan Kendal regency, Central Java.